We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
291
3
avatar+866 

The roots of the quadratic equation \(z^2 + az + b = 0\) are \(2-3i\)  and \(2+3i\). What is \(a+b\)?

 May 6, 2018
 #1
avatar+985 
+12

Hi ant101!

 

We use the rule that states:

 

In the quadratic equation \(ax^2+bx+c=0\)

 

The sum of the roots is \(-\frac{b}{a}\)

 

The produdct of the roots is \(\frac{c}{a}\)

 

In your question, the sum of the two roots is \(2-3i+3i+2=4\)

 

The product is, \((2-3i)(2+3i)\)

 

Using \(a^2-b^2=(a-b)(a+b)\)

 

\((2-3i)(2+3i)=2^2-(3i)^2=4-(9\cdot(-1))=4+9=13\)

 

Using the law, \(-\frac{a}{1}=4 \\ \frac{b}{1}=13\)

 

\(a=-4 \\ b=13 \\ 13+(-4)=\boxed9\)

 

That is the answer you seek.

 

I hope this helped,


Gavin

 May 6, 2018
edited by GYanggg  May 7, 2018
 #2
avatar+866 
+7

Amazing! Beautiful, Gavin! 

ant101  May 6, 2018
 #3
avatar+985 
+10

Thanks, I'n just glad I can help. 

GYanggg  May 6, 2018

13 Online Users

avatar
avatar